Reparations, Hyperinflation, Unemployment and the Rise of Adolph Hitler - Thies , Clifford F. (Studia Historiae Oeconomicae, 2024)
This paper reviews the history of the period 1918 to 1932 mostly to clarify the connections among the Treaty of Versailles, the German Hyperinflation of the 1920s, and the Great Depression of the 1930s to the rise of Adolph Hitler. In many cases, the paper takes a fresh look at original source material; and, it incorporates much of what has been subsequently written. While there are many lessons to be learned from these events, on the matter of reparations, the lesson is strange. In spite of Germany arguably not paying one pfenning of the demanded reparations, the demand for huge reparation payments contributed to the hyperinflation. More importantly, the re-negotiation of reparation payments enabled, first, Ludendorff and, then, Hitler to make gains in the polls. In the case of Hitler, his rise in the polls came just prior to the Great Depression of the 1930s.